Development of 3D Bio printed Tissue Models for Testing Drug Efficacy in Liver Diseases - Singh, Ranjit; De Mukhopadhyay, Keya; Yadav, Prachi; YC, Pallavi; Samajdar, Debojit (Journal of Neonatal Surgery, 2025)
The liver diseases of public health importance include hepatitis, cirrhosis, and liver cancer and there is a need to develop drugs for these diseases and evaluate them. The current models such as the 2D cell cultures and animal models do not mimic the functionality of human liver tissue, hence high drug failure rates and safety concerns. This paper will therefore aim to discuss the innovations of 3D bio-printed liver tissue models as new technologies in drug effects, safety, and metabolism. The goal here is to do away with the demerits of conventional testing and get more data on human liver performance. Liver tissue organ-on-a-chip models were developed using hepatocytes, endothelial cells, and stellate cells in a biomatrix through 3D bioprinting. The tissues generated through bioprinting were tested for their mechanical strength, electrical conductivity, and for their ability to metabolize drugs. The liver models developed through 3D bioprinting were described to possess structural and functional properties of normal liver tissue. Other cellular functions including albumin synthesis and cytochrome P450 enzyme activity also improved when compared with the 2D culture system. The models showed an enhanced ability to forecast hepatotoxicity and drug metabolism; thus, the applicability of these models in drug discovery and development was confirmed. Three-dimensional bioprinted liver tissue models are more physiological than two-dimensional cell cultures and hence more effective in drug testing. They provide a better understanding of how drugs operate and how deadly they are and might help in changing the concept of animal models and in the development of the idea of personalized medicine. More studies should be directed towards the difficulties linked with vascularization and the stability of the model for it to be used to its maximum potential.